PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL RIAS FOTO BERWARNA IGARI LOOKS PADA HASIL BELAJAR SISWA KELAS XI SMK NEGERI 8 SURABAYA - Ananda Fadiyah Arsya; Mutimmatul Faidah; Sri Dwiyanti; Novia Restu Windayani, (Jurnal Tata Rias, 2025)
This research focuses on the development of an instructional learning medium in the form of a video tutorial for colored photo makeup with the Igari Looks style, aimed at supporting learning outcomes in photo makeup competency. The study employed a research and development (R&D) approach using the ADDIE model. The research subjects were 29 students from SMK Negeri 8 Surabaya. The results of the study show that: (1) The development process of the video tutorial as a learning medium underwent expert validation and student trials, resulting in a rating categorized as "highly feasible". (2) The validation results indicated average percentages of 91.25% for the media aspect, 90% for the material aspect, and 88.25% for the language aspect, with an overall average of 89.83%. Based on these results, the video tutorial learning medium is deemed suitable for use in the teaching and learning process.